Fabio Baudrit Moreno Agricultural Experiment Station (EEAFBM): its evolution in the 20th century - Araya Villalobos, Rodolfo (2025)
The Fabio Baudrit Moreno Agricultural Experiment Station (EEAFBM) is located in the district of San José de Alajuela, Alajuela, Costa Rica (10°00′26″N, 84°15′57″W, at 840 m a.s.l.). It is a unit attached to the Faculty of Agricultural Sciences at the University of Costa Rica (UCR), dedicated to carrying out multidisciplinary work in research, teaching, and social outreach, in line with the objectives established in the UCR Statute, and contributing to the agricultural development of the country. This document describes the acquisition of the EEAFBM lands, the pioneers in its establishment and evolution, the beginning of research and extension programs, the successful collaborative work with governmental and international institutions, as well as the support provided to the agricultural sector during the 20th century, which continues into the 21st century. In addition, it includes the scientific outreach methods of the Experimental Station. This review also pays tribute to agronomist Fabio Baudrit Moreno, as the driving force behind the acquisition, management, initial leadership, and launch of the first research and teaching activities at the EEAFBM